Innovative Mycotoxin Detoxifying Agents Decrease the Absorption Rate of Aflatoxin B1 and Counteract the Oxidative Stress in Broiler Chickens Exposed to Low Dietary Levels of the Mycotoxin - Matteo Cuccato; Neenu Amminikutty; Veronica Spalenza; Vanessa Conte; Stefano Bagatella; Donato Greco; Vito D’Ascanio; Francesco Gai; Achille Schiavone; Giuseppina Avantaggiato; Carlo Nebbia; Flavia Girolami (Toxins)
Aflatoxin B1 (AFB1) can impair the growth of chickens and reduce the quality of eggs and meat, resulting in significant economic losses. The inclusion of mycotoxin detoxifying agents (MyDA) with binding properties in the diet is an efficient tool to reduce their absorption rate in the gastrointestinal tract. Our aim was to investigate the ability of two innovative MyDA (SeOX, a feed additive featuring a tri-octahedral smectite mixed with lignocellulose, and CHS, a di-octahedral smectite functionalized with an organic non-toxic modifier) in both reducing the bio-accessibility and mitigating the adverse effects of AFB1 in broilers exposed for 10 days to concentrations approaching the European Union maximum limits in feed (0.02 mg/kg). The amount of AFB1 in the excreta of birds, collected over four consecutive days (starting on day 7), was significantly lower (p < 0.001) in the group exposed to AFB1 alone compared to the groups treated with either SeOX or CHS. The calculated bio-accessibility was decreased by nearly 30% with both MyDA. This positive effect was reflected by a significant reduction (p < 0.001) in the oxidative stress (measured as serum antioxidant capacity and hepatic lipid peroxidation) induced by AFB1. Although antioxidant enzyme activities and glutathione levels were unaffected by any treatment, AFB1 significantly induced (p < 0.001) the upregulation of CYP2A6 and the downregulation of Nrf2; the latter was reverted by each MyDA. Overall, these results demonstrate that the selected MyDA are effective in limiting the AFB1 absorption rate, thereby mitigating or even reverting the oxidative stress induced by AFB1 in broilers.